Evaluación de la implementación de biosurfactantes en los procesos de recuperación mejorada de petróleo (EOR) mediante simulación numérica (2021)
Improving the performance of Enhanced Oil Recovery (EOR) processes is of vital importance in the oil industry, because the number of mature fields will continue to grow and each year more fields will exceed their production peak. Emerging chemical recovery technologies are an efficient alternative to reduce the amount of oil remaining originally on site after conventional extraction techniques are carried out. However, the chemical substances used, in addition to being very expensive, are of synthetic origin, which means that they are not biodegradable and therefore are not friendly to the environment.